Granulate cutworm, Feltia subterranea (Fabricius) (Insecta: Lepidoptera: Noctuidae) - John L. Capinera (EDIS, 2013)
The granulate cutworm, Feltia subterranea (Fabricius) is the most commonly occurring cutworm in Florida, though it is rarely numerous enough to be a major pest. It is nocturnal through most of its life and lacks distinctive features in the larval and adult stage, so it often is overlooked, and its activities and damage are not fully appreciated. This 4-page fact sheet was written by John L. Capinera and published by the UF Department of Entomology and Nematology, May 2013.